2020
DOI: 10.15414/agrobiodiversity.2020.2585-8246.070-77
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential of Some Asteraceae Bercht. & J. Presl. Representatives

Abstract: Asteraceae Bercht. & J. Presl. is a large family of plants with a different direction of use, among which are medicine, decorative, dietary crops that widely have used in human life. Plant raw material of these plants is a source of biologically active compounds with numerous biological activities such as antioxidant, antimicrobial, anti-inflammatory, etc. This study was aimed to evaluate the antioxidant potential of selected plants from Asteraceae: Bidens ferulifolia (Jacq.) Sweet, Echinacea purpurea (L.) Moe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Antiradical activity of different extracts of Silphium spp. showed that methanol extracts of four investigated species stem had less values, the maximum values demonstrated water extracts of leaves, buds, or inflorescences (Shymanska et al, 2020).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Antiradical activity of different extracts of Silphium spp. showed that methanol extracts of four investigated species stem had less values, the maximum values demonstrated water extracts of leaves, buds, or inflorescences (Shymanska et al, 2020).…”
Section: Resultsmentioning
confidence: 88%
“…& J. Presl family includes 33 species and originated from Northern America (Clevinger and Panero, 2000;Peni et al, 2020). Representatives from this plant family are well-known as medicinal plants with different biological activities such as antioxidant (Shymanska et al, 2020), antifungal, and immunosuppressive (Wolski and Kędzia, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…(Vergun et al, 2023). Plants from Asteraceae species are characterized by high antioxidant activity of various plant parts (Shymanska et al, 2020). Most investigations with Echinacea species, as well-known representatives of Asteraceae, including antioxidant activity, are connected with E. angustifolia and E. purpurea (Pellati et al, 2004;Jukić et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…(Skybitska et al, 2015), Origanum vulgare L., Melissa officinalis L. (Rasmussen, 2011), Ocimum basilicum L., Mentha piperita L. (Svidenko et al, 2015a,b), Rosmarinus officinalis L. (Mňahončáková et al, 2019), Allium ursinum L. (Balaeva-Tichomirova and Leonovich, 2017), Malva verticillata L. (Mikhailova and Ebel, 2015), Symphytum spp. (Vergun et al, 2017) and other ones (Vergun et al, 2018(Vergun et al, , 2019(Vergun et al, , 2021Shymanska et al, 2020).…”
Section: Introductionmentioning
confidence: 99%